Gait Is Associated with Cognitive Flexibility: A Dual-Tasking Study in Healthy Older People - Hobert, Markus A.; Meyer, Sinja I.; Hasmann, Sandra E.; Metzger, Florian G.; Suenkel, Ulrike; Eschweiler, Gerhard W.; Berg, Daniela; Maetzler, Walter (Frontiers in Aging Neuroscience, 2017)
OBJECTIVES: To analyze which gait parameters are primarily influenced by cognitive flexibility, and whether such an effect depends on the walking condition used. DESIGN: Cross-sectional analysis. SETTING: Tübingen evaluation of Risk factors for Early detection of Neurodegenerative Disorders. PARTICIPANTS: A total of 661 non-demented individuals (49-80 years). MEASUREMENTS: A gait assessment with four conditions was performed: a 20 m walk at convenient speed (C), at fast speed (F), at fast speed while checking boxes (FB), and while subtracting serial 7s (FS). Seven gait parameters from a wearable sensor-unit (McRoberts, Netherlands) were compared with delta Trail-Making-Test (dTMT) values, which is a measure of cognitive flexibility. Walking strategies of good and poor dTMT performers were compared by evaluating the patterns of gait parameters across conditions. RESULTS: Five parameters correlated significantly with the dTMT in the FS condition, two parameters in the F and FB condition, and none in the C condition. Overall correlations were relatively weak. Gait speed was the gait parameter that most strongly correlated with the dTMT (r2 = 7.4%). In good, but not poor, dTMT performers differences between FB and FS were significantly different in variability-associated gait parameters. CONCLUSION: Older individuals need cognitive flexibility to perform difficult walking conditions. This association is best seen in gait speed. New and particularly relevant for recognition and training of deficits is that older individuals with poor cognitive flexibility have obviously fewer resources to adapt to challenging walking conditions. Our findings partially explain gait deficits in older adults with poor cognitive flexibility.